Rediscovery and lectotypification of Lepidagathis clavata (Acanthaceae), a steno-endemic species from the northern Western Ghats, India - Kolte, Rutuja Rajendra; Kambale, Sharad Suresh; Gnanasekaran, Gunadayalan; Janarthanam, Malapati Kuppuswamy (Phytotaxa, 2016)
Lepidagathis clavata (Acanthaceae) is rediscovered after a lapse of 166 years from Chorla Ghat (type locality) in Karnataka and Chaukul plateau in Maharashtra from the northern Western Ghats, India. Besides, this name is lectotypified here, and the revised description and colour photographs are provided for an accurate and easy identification of this steno-endemic species.